(untitled) (Ibrahim Medical College Journal, 2014)
The aim of this study was to evaluate the efficacy of MRSA Chrome agar to detect methicillin resistant Staphylococcus aureus (MRSA) and compare it with 1?g oxacillin disc diffusion tests and detection of mecA gene by PCR. A total 116 Staphylococcus aureus (S. aureus), isolated from various clinical samples, were obtained from three tertiary care hospitals of Dhaka city. S. aureus was identified by colony characters, Gram stain and standard biochemical procedures. MRSA was detected by susceptibility to 1?g oxacillin disc, growth of denim blue color colonies of S. aureus on the Brilliance MRSA Chrome agar at 24 and 48 hours of incubation. PCR was performed for amplification of mecA gene as a gold standard method. Out of 116 isolated S. aureus, 33 (28.44%) were MRSA by oxacillin disc diffusion test where mecA gene was detected in 28 strains. On MRSA Chrome agar, 29 (25.0%) S. aureus produced denim blue colonies at 24 hours, of which 28 isolates possessed mecA gene. At 48 hours incubation, an additional 4 isolates yielded denim blue colonies from which mecA gene could not be identified. All the strains of S. aureus that produced denim blue colonies at 24 and 48 hours were resistant to oxacillin. The sensitivity, specificity and accuracy of oxacillin disc diffusion test were 100%, 94.31% and 95.68% and Chrome agar at 24 hours were 100%, 98.86% and 99.13% respectively. Thus MRSA Chrome agar could be good choice in clinical microbiology laboratory for rapid and accurate identification of MRSA. DOI: http://dx.doi.org/10.3329/imcj.v7i1.17697 Ibrahim Med. Coll. J. 2013; 7(1): 1-4